Commonalities and Peculiarities of the Return to Life of Holocaust Survivors in their Home Countries: The Dutch and Greek Cases in Context - Michman, Dan (Historein, 2019)
This article provides a survey of the main characteristics of the return process of Jewish survivors of the Holocaust to their home countries in the immediate aftermath of the Second World War, with the goal to contextualise and compare the return to the Netherlands and Greece.